2018
DOI: 10.1016/j.rboe.2017.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Trans-olecranon fossa four-cortex purchase lateral pinning in displaced supracondylar fracture of the humerus – a prospective analysis in 48 children

Abstract: ObjectiveThe current study aims at a functional analysis of trans-olecranon lateral pinning for displaced supracondylar fracture of the humerus (SCFH) in children.MethodsA prospective study of 48 children (30 males, 18 females; mean age: 7.4 years) with displaced SCFH was treated at this institution with modified technique from March 2011 to September 2014. Cases were selected on the basis of inclusion criteria. The functional outcome was assessed clinically by modified Flynn's criteria along with achievement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…A comparison of the functional outcome of the TOF-FCP method fixation in our study with that carried out by Kasirajan et al in 2017 showed similar functional outcome. 2 In our clinical study, out of 17 cases 100% showed excellent and good results which is similar to study by Kasirajan which had 96% satisfactory outcome. For cosmetic outcome the mean carrying angle in our study with its standard deviations was well within the range of the same obtained in other similar studies (Table 6).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…A comparison of the functional outcome of the TOF-FCP method fixation in our study with that carried out by Kasirajan et al in 2017 showed similar functional outcome. 2 In our clinical study, out of 17 cases 100% showed excellent and good results which is similar to study by Kasirajan which had 96% satisfactory outcome. For cosmetic outcome the mean carrying angle in our study with its standard deviations was well within the range of the same obtained in other similar studies (Table 6).…”
Section: Resultssupporting
confidence: 88%
“…Recently 'trans-olecranon fossa-four cortex purchase (TOF-FCP)' pin fixation technique has reports of having better torsional stability than conventional LOP and retaining its fewer complications. 2 But it affects mobility at elbow with early stiffness. Therefore, we conducted this prospective study to compare the outcome of all the three constructs for cosmetic and functional outcomes and complications comparison.…”
Section: Introductionmentioning
confidence: 99%